Spirit of the Paekche [videorecording] - Chung, Jaeshin; Heo, Baekkyu; Kim, Kidong; Song, Hwa. ([S.l.] Arirang TV)
A journey through the south Chungchong province. Explores the ginseng market, traditional houses, ceramic art villages, pottery and folk festivals.
This program is sponsored by The Korea Foundation.
VHS.
Director of photography, Bae Sunjoo ; editor, Jang Bosun ; narrator, Michael MacInnis.
Keywords: Architecture -- Korea; Festivals -- Korea; Paekche (Korea) -- Description and travel; Paekche (Korea) -- Social life and customs; Korea -- Antiquities; Paekche (Korea) -- History; ASIAN HISTORY; SOCIOLOGY; GEOGRAPHY; ARTS; ARCHITECTURE